Uma psicologia da religião: estudo sobre o desenvolvimento da consciência pelo processo de simbolização - Fernandes, Roberto Rosas (2009)
The main purposes of this thesis are to approach the development of conscience through symbolic elaboration and to study narcissism as an impulse and, simultaneously, an obstacle to that process. Narcissism becomes an obstacle, when it was not enough mirrored during the first years of a person s life. This study offers an archetypal map of the most expressive tendencies that are observed at the clinical psychology practice, regarding the Self s yearning for overcoming archaic ways of being in the world, so as to reach other ways of doing so in more complete and comprehensive manners, just as religions, in their specific mode, have so well described. Therefore, this study is based on clinical observation, in which the differentiation movement from incestuous relationships becomes evident during to the search of the individual s center. This thesis assumes that there are affinities between the religious search and the natural flux of the psychodynamics and emphasizes the possible connection between the psychological study and the religious institutions. Through this study, people who are devoted to take care of the human soul may access the most significant findings of those who dedicated their lives to the study of the psychodynamics. This thesis is destined to psychologists, priests, and teachers that focus on facilitating the human development